Optimal replenishment time for retailer under partial upstream prepayment and partial downstream overdue payment for quadratic demand. Issue 1 (2nd January 2018) - Shah, Nita H.; Jani, Mrudul Y.; Chaudhari, Urmila
ABSTRACT: In competitive edge, the proffer of delay payment is of great consequence tool to boost the market demand by exerting influence of more customers. In opposition to, merchandiser may be asked to pay some per cent of purchasing cost before receiving products to reduce the risk of cancellation of order. In this article, optimal replenishment time for merchandiser under partial upstream prepayment and partial downstream overdue payment is presented under quadratic demand with three different models: (1) without deterioration, (2) with constant deterioration and (3) maximum fixed-lifetime deterioration as loss of utility is the real situation of products like fruits, vegetables, juices, etc., and to reduce deterioration of the product, merchandiser spends capital on preservation technology to preserve the item. Quadratic demand is suitable for the products for which demand increases initially and afterward it starts to decrease. The decision policies are analysed for the merchandiser. The objective is to minimize merchandiser's total cost with respect to decision variables. The models are supported with numerical examples. Sensitivity analysis is carried out to derive insights for decision maker.